Raising the Roof: The Pastoral-to-Program Size Transition - Mann, Alice (Rowman & Littlefield Publishers, 2001)
Pastoral-to-program size change is frequently described as the most challenging of growth transitions for congregations. Now Alban senior consultant Alice Mann, author of The In-Between Church: Navigating Size Transitions in Congregations, addresses the difficulties of that transition in this resource designed specifically for a congregational learning team. Conceptualized and developed by Mann for an Alban on-line seminar program test event conducted with 12 congregations in transition, her newest book features a five-step process enabling the learning team to engage a wider circle of congregational leaders and members in study, discernment, and planning. Never-before published resources include discussion of a major new concept—passive barriers to growth—plus Mann’s "System Change Index" tool to help congregations measure their progress from pastoral-size to program-size ways of operating. From preparing the congregation’s board and members, selecting the person to guide the learning process, and recruiting the learning team, to creating and celebrating a plan for congregational learning and action, Mann provides all the resources a congregation needs to address this significant size transition period.